Dysgraphia in Alzheimer's Disease: A Review for Clinical and Research Purposes. - Neils-Strunjas, Jean; Groves-Wright, Kathy; Mashima, Pauline (Journal of Speech, Language & Hearing Research, 2006)
Purpose: This article presents a critical review of literature on dysgraphia associated with Alzheimer's disease (AD). Research presented includes discussions of central and peripheral spelling impairments as well as the impact of general, nonlinguistic cognitive functions on dysgraphia associated with AD. Method: The studies critically reviewed were from a variety of disciplines, with emphasis on seminal work, recent literature, and the first author's research. Conclusions: Studies have shown that writing impairment is heterogeneous within the AD population; however, there are certain aspects of the writing process that are more vulnerable than others and may serve as diagnostic signs. Identifying patterns of writing impairment at different stages of AD may help to chart disease progression and assist in the development of appropriate interventions. Reprinted by permission of the publisher.